2019
DOI: 10.1002/fsn3.886
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol, fatty acid, and phytochemical profiles in a new red sorghum variety (Ji Liang No. 1) and its antioxidant and anti‐inflammatory properties

Abstract: In this study, a new red sorghum variety (Ji Liang No. 1) was investigated for its triacylglycerol ( TAG ) and fatty acid profiles, carotenoid and tocopherol compositions, total phenolic, total flavonoid and phenolic acid contents, and antioxidant and anti‐inflammatory properties. A total of 17 TAG s were identified in the red sorghum oil. Linoleic and oleic acids were the primary fatty acids, contributing more than 80% of the total fatty acids. β‐Carotene was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Several in vitro studies have reported on the strong antioxidative and anti-inflammatory capacity of sorghum compounds [ 5 , 6 ]. Moreover, sorghum consumption may be beneficial for the prevention of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have reported on the strong antioxidative and anti-inflammatory capacity of sorghum compounds [ 5 , 6 ]. Moreover, sorghum consumption may be beneficial for the prevention of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Speciality grain sorghum is reported to contain bioactive compounds such as phenolic compounds, including phenolic acids (benzoic and cinnamic acids), flavonoids (3-deoxyanthocyanidins), condensed tannins (proanthocyanidins, flavin-3-ols), lignin and stilbenes produced through phenylpropanoid pathway [9,16] possessing anti-microbial activity, and anti-inflammatory and anticancer activities [49,50]. Several in-vitro studies have reported on the strong anti-oxidative and anti-inflammatory capacity of sorghum compounds [51,52]. According to the phenolic profile and color, sorghum is broadly classified into five types: white, black, brown, red and yellow [40].…”
Section: Discussionmentioning
confidence: 99%
“…Blank group was treated with DMEM only; LPS group was treated with LPS only; LPS + extracted gypenosides groups were pretreated with different concentrations of gypenosides for 1 hr and then stimulated with LPS (1 μg/ml) for 4 hr. RNA isolation and quantitative real‐time polymerase chain reaction (qRT‐PCR) were conducted according to a laboratory protocol (Zhang et al, ). Specific forward and reverse primer sequences used in this study were shown as follows: IL‐6 (Forward: 5′‐CACGGCCTTCCCTACTTCAC‐3′, Reverse: 5′‐TGCAAGTGCATCATCGTTGT‐3′); IL‐1β (Forward: 5′‐GTTGACGGACCCCAAAAGAT‐3′, Reverse: 5′‐CCTCATCCTGGAAGGTCCAC‐3′); TNF‐α (Forward: 5′‐CGAGTGACAAGCCTGTAGC‐3′, Reverse: 5′‐GGTGTGGGTGAGGAGCACAT‐3′); COX‐2 (Forward: 5′ ‐GGGAGTCTGGAACATTGTGAA‐3′, Reverse: 5′ ‐GCACGTTGATTGTAGGTGGACTGT‐3′); and β‐actin (Forward: 5′‐GGAATGGGTCAGAAGGACTC‐3′, Reverse: 5′‐CATGTCGTCCCAGTTGGTAA‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…Blank group was treated with DMEM only; LPS group was treated with LPS only; LPS + extracted gypenosides groups were pretreated with different concentrations of gypenosides for 1 hr and then stimulated with LPS (1 μg/ml) for 4 hr. RNA isolation and quantitative real-time polymerase chain reaction (qRT-PCR) were conducted according to a laboratory protocol (Zhang et al, 2019). Specific forward and reverse primer sequences used in this study were shown as follows: IL-6 (Forward: 5′-CACGGCCTTCCCTACTTCAC-3′, Reverse:…”
Section: Rna Extraction and Rt-pcr Analysismentioning
confidence: 99%